PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 011 RANTAU PANJANG KIRI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Junaidi Junaidi; Damanhuri Daud; Munjuiatun Munjuiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problems of the background for this study is the low student learning outcomes. So the researchers conducted a study with the aim to improve learning outcomes IPA Elementary School students SDN 011 Rantau Panjang Kiri through the application of guided inquiry learning model. This research was conducted in March 2015. The subjects were students of class V Elementary School 011 Rantau Panjang Kiri with the number of students 23 people consisting of 10 men - men and 13 women. Design of this research is classroom action research with two cycles. Which was held from 12 March 2015 to 17 April 2015. The results showed an increase in activity of student learning and teacher. Increased student learning outcomes in the first cycle than before tindakkan namely a base score of 39.1% of the 23 students who completed the first cycle of students and to 65.2% of students who pass out of 23 students, and the second cycle becomes 91.3% of students the completion of 23 students. Teacher activity increased in the first cycle of the first meeting of the percentage of teachers activity by 60.0%, and the second meeting in the first cycle to 65.0% increase as much as 5%. In the second cycle the first meeting be 75.0%, and the second meeting of the second cycle of 90.0% increased by 15%. While the activities of students at the first meeting of the first cycle of 55.0%, and the second meeting in the first cycle of 65.0% increased by 10%, and the second cycle at the first meeting amounted to 75.0%, and at the second meeting of the second cycle to 95, 0% increased by 20%. Then the average - average yield increase student learning from a base score of 65.4, and the average - average in the first cycle increased to 69.6, an increase learning outcomes from the first cycle to the base score of 6.42%, further value - average cycle II also increased to 78.9, an increase learning outcomes of the second cycle to the base score of 20.64%. From the results of the study as described in the above that the use of guided inquiry learning model is correct then the teacher and student activities and student learning outcomes to be increased and better. This information proves that the hypothesis which says: If applicable, the guided inquiry learning model can improve learning outcomes IPA Elementary School fifth grade students 011 Rantau Panjang Kiri.Key word : Model Implementation Guided Inquiry Learning, to increase student learning outcomes IPA